Analisa Tingkat Kepatuhan Pasien Home Care dalam Minum Obat Anti Hipertensi - Adriyan Suhada; Musparlin Halid (Jurnal Penelitian dan Kajian Ilmiah Kesehatan Politeknik Medica Farma Husada Mataram, 2022)
Hypertension is often referred to as a hidden killer disease because this disease usually does not give specific symptoms to sufferers and is very dangerous. Compliance in taking hypertension medication is a major problem for patients so that many patients experience sudden attacks when their blood pressure rises. Providing home care with counseling is reported to provide patients with a better understanding of the disease and can improve the patient's quality of life. The purpose of this study was to determine the level of compliance of home care patients in taking anti-hypertensive drugs at Mitra Dasan Cermen Pharmacy, to determine the factors that influence the compliance of home care patients in taking anti-hypertensive drugs. The research method used was cross sectional using a compliance level questionnaire and a questionnaire of factors affecting the level of compliance, the data were analyzed by the spearman rank correlation test. The results showed that 57.6% of respondents had a moderate level of compliance 42.4% of respondents had a moderate level of compliance, 3 factors affecting the level of compliance that had a relationship, namely gender p = 0.001), education level (p = 0.000), family support (p = 0.001), 4 factors of compliance level that did not have a relationship, namely employment status (p = 0.189), duration of hypertension (p = 0.805), health insurance participation (p = 0.065).